A ação do habitus dos gestores na adoção de sistemas de informação : um estudo de caso em uma cooperativa de crédito - Lima, Ana Lucia Candeia de (2024)
The present study aimed to identify how managers' habitus acts the adoption of Information Systems (ISs). Embodied in the understanding that the habitus (way of being, thinking and acting) of agents structured by the accumulation of capital and field forces, is an explanatory factor for the adoption of ISs in the organizational field. To this end, the study is based on Pierre Bourdieu's Theory of Action, which presupposes that every individual has a habitus and is inserted in a social environment called field, whose interaction between them forms a structuring and structured structure, as they the field structures the agents' habitus while it is simultaneously structured by this same habitus (Bourdieu, 1987). The research was carried out through an interpretive single case study, with a singular credit cooperative as its locus. Data collection was carried out through observation, primary and secondary documents and semi-structured interviews with 8 managers from different hierarchical levels, both in elected and executive positions, guided by the model proposed by Freitag (2019), and analyzing the evidence collected through content analysis. The results indicated that the formation of the managers' habitus is mostly linked to the accumulation of acquired social capital, demonstrated by the agents' contact network within the field, and to the accumulation of cultural capital acquired by the agents throughout their career, especially after joining in the cooperative studied, demonstrated based on the qualifications of the managers. In this context, the study findings in relation to the managers' habitus raised a homogeneous class habitus, marked mainly by the agents' commitment to the cooperative and orientation towards change, during the process of management changes and changes in information systems. Thus, it can be inferred that the habitus of these managers is explanatory for the process of adopting ISs in the cooperative studied. This research contributes academically to the construction of the research framework on cooperativism in Brazil, contributes to the development of empirical knowledge about the stages and variables of the decision-making process in diffuse models, contributing to the construction of references for the creation of efficient and sustainable practices for cooperative management, and, contributes socially by developing a theoretical/empirical study in an associative model, which contributes to the development of the local community where it operates.